2022
DOI: 10.1371/journal.pbio.3001526
|View full text |Cite
|
Sign up to set email alerts
|

The NKCC1 ion transporter modulates microglial phenotype and inflammatory response to brain injury in a cell-autonomous manner

Abstract: The NKCC1 ion transporter contributes to the pathophysiology of common neurological disorders, but its function in microglia, the main inflammatory cells of the brain, has remained unclear to date. Therefore, we generated a novel transgenic mouse line in which microglial NKCC1 was deleted. We show that microglial NKCC1 shapes both baseline and reactive microglia morphology, process recruitment to the site of injury, and adaptation to changes in cellular volume in a cell-autonomous manner via regulating membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 91 publications
(162 reference statements)
2
33
0
Order By: Relevance
“…Further understanding of the underlying molecular mechanisms of how bumetanide regulates microglia function remains to be elucidated. NKCC1 is expressed in glial cells, and a single-cell transcriptomic study (BRAIN-SAT database) has supported NKCC1 expression in microglia ( 21 ), which consisted of a recent study showing microglial NKCC1 expression in the brain ( 45 ), but its role in neurodevelopment conditions like ASD remains unknown. Researchers found that bumetanide attenuated LPS-induced acute lung injury by inhibiting NKCC1-mediated macrophage volume alteration and inflammatory function in a mouse model of LPS-induced lung injury ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further understanding of the underlying molecular mechanisms of how bumetanide regulates microglia function remains to be elucidated. NKCC1 is expressed in glial cells, and a single-cell transcriptomic study (BRAIN-SAT database) has supported NKCC1 expression in microglia ( 21 ), which consisted of a recent study showing microglial NKCC1 expression in the brain ( 45 ), but its role in neurodevelopment conditions like ASD remains unknown. Researchers found that bumetanide attenuated LPS-induced acute lung injury by inhibiting NKCC1-mediated macrophage volume alteration and inflammatory function in a mouse model of LPS-induced lung injury ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the beneficial actions of NP(bumetanide) may be based on the anti-inflammatory action caused by the inhibition of NKCC1 in the microglia. However, there is an intriguing finding that the direct administration of bumetanide into the brain in vivo displayed the opposite effect of a systemic administration and can be explained by changes in K + efflux mechanism in microglia ( 45 ). Therefore, the precise mechanism through the NKCC1 inhibitor bumetanide modulates the function of microglia in BTBR mice needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive expression of P2Y12 receptors (P2Y12R) are widely considered to be a signature of microglia in the healthy brain (Bosco et al, 2018; Hickman et al, 2013; Peng et al, 2019), while downregulation of P2Y12R is generally observed in pathologies and associated with a reactive phenotype (Lin et al, 2021; Tóth et al, 2022; Zrzavy et al, 2017). Drastic downregulation of P2Y12Rs were observed in slice cultures as well, but changes were monitored in a longer timeframe (0, 8, 24 hours), and the extent has been shown to correlate strongly with microglia morphology (Haynes et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The extensive expression of P2Y12 receptors (P2Y12R) are widely considered to be a signature of microglia in the healthy brain (Bosco et al, 2018;Hickman et al, 2013;Peng et al, 2019), while downregulation of P2Y12R is generally observed in pathologies and associated with a reactive phenotype (Lin et al, 2021;Tóth et al, 2022;Zrzavy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%